Synergism of an auxiliary activity 9 (AA9) from Chaetomium globosum with xylanase on the hydrolysis of xylan and lignocellulose. Issue 10 (October 2016) - Kim, In Jung; Youn, Hak Jin; Kim, Kyoung Heon
Graphical abstract: Highlights: Auxiliary activity 9 from Chaetomium globosum ( Cg AA9) showed synergism with xylanase. AA9 increased the enzymatic hydrolysis of pure xylan and xylan in lignocellulose. This is the first report of synergism of AA9 with xylanase on pure xylan. Abstract: Auxiliary activity family 9 (AA9) is a group of fungal synergistic proteins belonging to the lytic polysaccharide monooxygenases. Via oxidative cleavage, AA9 facilitates cellulose hydrolysis by cellulase. However, oxidative activity of AA9 on pure xylan has not been reported yet. Previously, an AA9 from Chaetomium globosum ( Cg AA9) was identified and expressed in Escherichia coli . The recombinant Cg AA9 exhibited synergistic effects in cellulose hydrolysis. Here, we showed that Cg AA9 acts synergistically in xylan hydrolysis. When the insoluble fraction of xylan from beechwood was hydrolyzed by xylanase, Cg AA9 yielded 1.3 times more reducing sugar than that produced only by xylanase, and the extent of synergism by Cg AA9 was enhanced in the presence of ascorbic acid as a reducing cofactor. In addition, Cg AA9 functioned on pretreated rice straws. This is the first report of the synergistic activity of AA9 with xylanase in the hydrolysis of pure xylan and xylan contained in pretreated lignocellulose.